Philosophical foundations of constitutional law - Dyzenhaus, David; Thorburn, Malcolm, 1971- (Oxford, United Kingdom : Oxford University Press, 2016)
Constitutional law has been and remains an area of intense philosophical interest, and yet the debate has taken place in a variety of different fields with very little to connect them. In a collection of essays bringing together scholars from several constitutional systems and disciplines, Philosophical Foundations of Constitutional Law unites the debate in a study of the philosophical issues at the very foundations of the idea of a constitution: why one might be necessary; what problems it must address; what problems constitutions usually address; and some of the issues raised by the administration of a constitutional regime.
I. What is a constitution? -- The idea of a constitution : a plea for Staatsrechtslehre / David Dyzenhaus -- The unwritten constitution as a legal concept / Mark D. Walters -- On constitutional implications and constitutional structure / Aharon Barak -- Reflections on what constitutes "a constitution" : the importance of "constitutions of settlement" and the potential irrelevance of Herculean lawyering / Sanford Levinson -- Constitutional amendment and political constitutionalism : a philosophical and comparative reflection / Rosalind Dixon and Adrienne Stone -- II. Constitutional authority -- Constitutional legitimacy unbound / Evan Fox-Decent -- Constituent power and the constitution / Hans Lindahl -- Popular sovereignty and revolutionary constitution-making / Richard Stacey -- Constitutional reason of state / Thomas Poole -- III. Constitutional fundamentals -- The rule of law / T.R.S. Allan -- The constitutional separation of powers / Aileen Kavanagh -- The framework model and constitutional interpretation / Jack M. Balkin -- Philosophical foundations of judicial review / Cristina Lafont -- IV. Constitutional rights and their limitation -- Equality rights and stereotypes / Sophia Moreau -- Proportionality / Malcolm Thorburn.
Series statement from dust jacket.
Includes bibliographical references and index.
Keywords: Constitutional law -- Philosophy; Verfassungsrecht; Rechtsphilosophie; Constitutional law -- Philosophy